Experiences and perceptions of pregnant women diagnosed with gestational diabetes mellitus: A qualitative study - Lazarou, Eleftheria; Panteli, Theodosia; Metallinou, Dimitra; Lambrinou, Ekaterini; Kolokotroni, Ourania; Miltiadous, Panagiota; Hadjigeorgiou, Eleni (My University, 2025)
The current antenatal care for women diagnosed with gestational diabetes mellitus in Cyprus does not adequately address their informational and emotional needs, resulting in significant gaps in support and overall care quality.
Keywords: Cyprus; Experiences; GDM; Gestational diabetes; Perceptions; Pregnant women